Health-Related Physical Fitness in Patients With Inflammatory Bowel Disease vs Healthy Control Subjects. - Demers, Karlijn; van den Bergh, Noortje; Bongers, Bart C; Kuijk, Sander M J van; Mujagic, Zlatan; Jonkers, Daisy M A E; Pierik, Marieke J; Stassen, Laurents P S (Inflammatory Bowel Diseases, 2025)
Background Inflammatory bowel disease (IBD) may negatively affect health-related physical fitness. However, the development of interventions to improve health-related physical fitness and thereby disease outcomes is hindered by insufficient evidence. This study compared health-related physical fitness between patients with IBD and healthy control subjects, examined associations with disease and treatment characteristics, and explored patients' perspectives. Methods In this cross-sectional study, 105 patients with IBD and 102 age- and sex-matched healthy control subjects performed validated tests for body fat (4-site skinfold thickness), cardiorespiratory fitness (steep ramp test), muscular strength (steep ramp test, 60-second sit-to-stand test, hand-held dynamometry), muscular endurance (isokinetic dynamometry), and flexibility (sit-and-reach test). Data on disease and treatment characteristics, fatigue, physical activity, and patients' perspectives were collected. Results Patients with IBD had higher body fat (29.5% vs 26.9%; P  =  . 012), lower steep ramp test performance (peak work rate 4.2 W/kg vs 4.8 W/kg; P  <  . 001), fewer sit-to-stand repetitions (42 vs 47; P  =  . 002), and reduced hamstring strength (3.0 N/kg vs 3.2 N/kg; P  =  . 011) compared with healthy control subjects. This was associated with higher age, female sex, higher body mass index, fatigue, arthritis, and multiple biologicals used. Most patients considered physical fitness important and beneficial for their symptoms, and the majority expressed interest in professional support. Conclusions Patients with IBD have higher body fat and reduced cardiorespiratory fitness and muscular strength compared with healthy control subjects. Especially, patients with a higher age, female sex, higher body mass index, fatigue, arthritis, or multiple biologicals used are at risk for such impairments and may benefit from physical exercise interventions.